Assessment of the results of clinical pharmacists' interventions on the use of antibiotics at a medical center in Vietnam between 2021 and 2022 - Duyen Thi My Huynh; Chat Luong Luong; Quang Loc Duyen Vo; Ba Kien Tran; Van De Tran (GarVal Editorial Ltda., 2023)
Context: The rational use of antibiotics is a priority when antibiotic resistance has become severe. Clinical pharmacists' interventions can help increase the rate of rational antibiotic use. Aims: To determine the effect of clinical pharmacists' interventions on the use of antibiotics and factors related to inappropriate antibiotic use in inpatients at the Department of Surgery, Gia Rai Town Medical Center, Vietnam. Methods: An interventional and cross-sectional descriptive study was conducted from January 1, 2021, to June 30, 2022, at the Department of Surgery, Gia Rai Town Medical Center, Vietnam. Results: There were 710 patients (355 patients in pre-intervention and 355 patients in post-intervention) included in this study. The group of antibiotics used the most was beta-lactam (pre- and post-intervention rates were 60.2% and 61.0%, respectively). The parenteral route was the most commonly used (63.9% in pre-intervention and 60.7% in post-intervention). The rationality of the indication increased after the intervention (from 85.7% to 96.2%); the rationality of the dose increased after the intervention (from 90.5% to 95.2%); the rationality of the number of times of use increased after the intervention (from 90.4% to 98.4%); the rationality of the time increased after the intervention (from 94.8% to 95.1%); the general rationality increased after the intervention (from 66.5% to 85.6%). Infections were associated with inappropriate antibiotic use (p<0.05). Conclusions: Effective clinical pharmacists' interventions helped raise the rate of rational use of antibiotics. Besides, inappropriate antibiotic use was found to be associated with infections, emphasizing the need for targeted interventions in this field.